1991
DOI: 10.1080/03014469100001732
|View full text |Cite
|
Sign up to set email alerts
|

Age changes in adult stature: trend estimation from mixed longitudinal data

Abstract: Although it is widely accepted that persons become shorter as they grow older, most estimates of the rate of decline are based largely on cross-sectional studies and are confounded by secular changes and individual variation. The present study uses a mixed series of longitudinal physical measurements, obtained by the Busselton Population Studies Group, for nearly the entire adult population of Busselton, Western Australia. All persons in the sample who had a minimum of three measures at 3-year intervals are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…Studies on body height have found that height declines with age: this is more common in women than in males (de Groot et al, 1996;Allen, 1989). Although it is widely accepted that persons become shorter as they grow older (Chandler & Bock, 1991), this excess loss of height in females with advancing age re¯ects the existing osteoporotic condition (Gunnes et al, 1996).…”
Section: Heightmentioning
confidence: 99%
“…Studies on body height have found that height declines with age: this is more common in women than in males (de Groot et al, 1996;Allen, 1989). Although it is widely accepted that persons become shorter as they grow older (Chandler & Bock, 1991), this excess loss of height in females with advancing age re¯ects the existing osteoporotic condition (Gunnes et al, 1996).…”
Section: Heightmentioning
confidence: 99%
“…The effect of weightaheight 2 on mortality was assessed using an estimation of peak adult height 17 with little change in the nature of the associations. The effect of weightaheight 2 was also analysed after adjustment for coronary heart disease risk factors (total cholesterol, systolic and diastolic blood pressure, smoking) as well as for age, without altering the relationships qualitatively, although the signi®cance levels were reduced.…”
Section: Additional Analysesmentioning
confidence: 99%
“…The dispersion is, however, greater in the present population. This is most probably due to greater inter-individual variations in loss of stature in older persons [20]. In addition, the ratio of BMIs based on arm span and height, respectively, was close to 1, but with rather great dispersion.…”
Section: Discussionmentioning
confidence: 89%